Odpowiedzi

2009-10-28T11:17:16+01:00
Lewa strona= (tgx+1)²=tg²x+2tgx+1=(sinx/cosx)²+2tgx+1=
sin²x/cos²x+2tgx+1 w pierwszym wyrazeniu wykorzystuje jedynke trygonometryczna tzn.sin²x+cos²x=1 i mam

L= (1-cos²x)/cos²x+2tgx+1 rozbijam ulamek na 2
L=1/cos²x-cos²x/cos²x+2tgx+1=1/cos²x-1+2tgx+1=1/cos²x+2tgx=P

cnu.
Najlepsza Odpowiedź!
2009-10-28T11:21:50+01:00
(tgx+1)² = 1/cos²x + 2tgx
L.:(tgx+1)²=tg²x+2tgx+1=(sinx/cosx)²+2sinx/cosx+1=
sin²x/cos²x+2sinx/cosx+1=
[sin²x+2sinxcosx+cos²x]/cos²x=[1+2sinxcosx]/cos²x

P:1/cos²x + 2tgx =[1+2tgx*cos²x]/cos²x=[1+2*sinx/cosx*cos²x]/cos²x=
[1+2sinxcosx]/cos²x
Zatem L=P